Internet of Things and Blockchain Revolutionary Integration in the Business and Financial Sector - Lal, Karu; Thaduri, Upendar Rao; Dekkati, Sreekanth (Asian Business Review, 2022)
Many applications of the Internet of Things have been developed, and these applications are causing people's lifestyles to shift. The Internet of Things (IoT) finance refers to the various applications of the Internet of Things that have the potential to extend financial services throughout the entirety of the IoT commodities transaction, subvert traditional finance & Internet finance services, and make the financial business processes more intelligent, transparent, and accurate. This article presents the design and implementation of a financial management platform based on combining blockchain technology with supply chain logistics. Supply chain finance is integrated using blockchain technology to synchronize the system of bank account payments, achieve the automatic flow of funds, process supervision, and automatically settle account periods based on smart contracts. Therefore, this research paper aims to discuss the function of blockchain technology within the Internet of Things (IoT) and financial applications. These two domains stand to benefit the most from its implementation. In addition, this study investigates the concerns regarding privacy and security associated with it and offers some thoughts regarding how these issues can be addressed. In the final step of this process, the public perception of blockchain technology addresses how various parts of society view blockchain technology.